Facile and Stereo-Selective Synthesis of UDP-α-D-xylose and UDP-β-L-arabinose Using UDP-Sugar Pyrophosphorylase - Wang, JiaJia; Greenway, Harmon; Li, Shanshan; Wei, Mohui; Polizzi, Samuel J.; Wang, Peng G. (Frontiers in Chemistry, 2018)
A novel synthesis of nucleotide sugars was conducted to prepare UDP-α-D-xylose and UDP-β-L-arabinose without utilizing protection strategies or advanced purification techniques. Sugar-1-phosphates of D-xylose and L-arabinose were synthesized from their β-glycosylsulfonylhydrazides and evaluated as substrates for recombinant UDP-sugar pyrophosphorylases from Arabidopsis thaliana or Bifidobacterium infantis to furnish the biologically active nucleotide. The facile, three-step procedure takes advantage of substrate diversity available through chemical synthesis followed by the selectivity of enzyme catalysis. This approach increases the substrate scope of enzymatic preparation and expands access to stereopure nucleotide sugars on preparative scale. Increased production of both sugars has implications for glycoengineering and glycan production using glycosyltransferases.